EFFECT OF BUSINESS RISK, FIRM SIZE, SALES GROWTH, PROFITABILITY AND LIQUIDITY ON CAPITAL STRUCTURE IN FOOD AND BEVERAGE SECTOR MANUFACTURING COMPANIES LISTED IN EXCHANGE OF INDONESIA STOCK (BEI) 2013-2017 - Gurusinga, Latersia Br (International Journal of Public Budgeting, Accounting and Finance, 2019)
The purpose of this study is to analyse the components of business risk, firm size, sales growth, profitability and liquidity influencing the capital structure of food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2013-2017. This research was conducted by observing the food and beverage sector manufacturing companies on the Indonesia Stock Exchange. The sampling technique uses a sampling census method where. Testing the hypothesis by regression of the data panel and analysis is done using the Eviews application tool. The results of this study prove that partially business risk variables and firm size affect the capital structure while the sales growth, profitability and liquidity variables do not affect the firm value.